Key to species of the genus Fistulatus Zhang, 1997 (Hemiptera: Cicadellidae: Deltocephalinae: Drabescini) with description of two new species from China - Yang, Yanqiong; Dai, Renhuai; You, Siying (Zootaxa, 2024)
The leafhopper genus Fistulatus Zhang, 1997 (Cicadellidae: Deltocephalinae: Drabescini: Paraboloponina) is reviewed with descriptions of two new species, Fistulatus biconjugara sp. nov., from Guizhou Province, China and F. brevimarginalis sp. nov., from Yunnan Province, China. A checklist with distributions and a key to males of this genus are provided. The specimens studied are deposited in the Institute of Entomology, Guizhou University, Guiyang, Guizhou, China (GUGC).